SMART AMBULANCE TRAFFIC CONTROL SYSTEM - SUREN, KRISHNAN (Universiti Malaysia Sarawak (UNIMAS), 2020)
Smart Ambulance Traffic Control System is integrated system between the traffic light and the ambulance. The traffic light can be controlled every time there is an ambulance approaching. Radio-Frequency Identification (RFID) is used as instrument to communicate with traffic lights in the case of traffic is congested. The driver of the ambulance needs to activate the RFID tag to allow the detection RFID readers and detection control the traffic light operation.